Presencia de la enfermedad del mal de azúcar (Sphacelia spp.) en tres especies del pasto Brachiaria (Panicoidea, Poaceae) - García, S.X.; Pineda López, Benjamín; Salazar Erazo, Sandra Milena (2001)
The increase and regeneration of Brachiaria germplasm are carried out, under field conditions at "Santa Rosa" Experimental station near Popayan where the seed production conditions are relatively good. Nevertheless under the conditions of precipitation (more than 2000mm) and temperature (16-24 °C) of this location the production of seeds can be affected by fungal diseases. In a fungal diseases survey, during the second semester of 1999 and the first of the 2000, a honeydew oozing was observed on flowers when flowering was starting. Later the apparition of fungal growths of white color, black, green or pink in individual or combined form was observed on the affected seeds. The field observations on Brachiaria brizantha, Brachiaria decumbens and Brachiaria jubata multiplication plots allowed to determine that the disease affected the inflorescences with several grades of severity. The studies carried out in the Germplasm Health Laboratory (GHL) of the Genetic Resources Unit (GRU), consistent in a microscopic study of the oozed, cultivation in PDA and isolation starting from affected flowers, and pathogenicity tests allowed to determine that affection was the Honeydew disease occasioned by a species of Sphacelia. This pathogen produced conidia of several size and form, some of them (macroconidia): oval (13.76 x 5.2 ?u), pyriform (14,04 x 5,51?m) or spherical microconidia (4.64 m?). The colored fungal fructifications according to the laboratory analysis were classified as Cerebella sp., (Epicoccum sp.), Cladosporium sp., y Fusarium sp. In order to verify the association of Sphacelia sp. with the seeds, seed samples of 18 accesions of B. brizantha, seven of B. decumbens and five of B. jubata were gathered. The seeds were conditioned according to the procedures established in the GRU for the gramìnae germplasm and carried out their analysis of seed health in the GHL using washing test in order to verify the presence of Sphacelia conidia on seeds. The obtained results showed that the studied seed accessions were contaminated by Sphacelia spp.